Business Result. Advanced ыtudent's Book - Baade K. Kate; Holloway C. Christopher; Scrivener J. Jim.; Turner R. Rebecca (New York, Oxford University Press, 2009)
Learn the communication skills you need at work today. Communicative syllabus provides pick-up-and-use business skills Interactive Workbook on CD-ROM offers flexibility and self-study options Real-world case studies include the Expert View - professional commentary from experts at Cranfield School of Management Multimedia support for teachers and studentsInteractive Workbook on CD-ROM with the Student's Book includes practice exercises, sample emails and tests for every unit, plus an interactive phrasebank and an interactive glossary Teacher training DVD with the Teacher's Book shows Business Result in action in the classroom Business Result student's website for more practice-. www.oup.com/elt/result Case studies with the Expert View Every Business Result case study is validated by expert input from Cranfield School of Management. The Expert View provides real-world business authenticity and introduces an authoritative business perspective to your lessons.